2017
DOI: 10.1002/ajh.24738
|View full text |Cite
|
Sign up to set email alerts
|

Renal outcomes in patients with AL amyloidosis: Prognostic factors, renal response and the impact of therapy

Abstract: A staging system for patients with renal AL amyloidosis, based on eGFR (<50 ml/min/1.73 m ) and proteinuria (≥5 g/day) at diagnosis, as well as criteria for renal progression (≥25% eGFR reduction) and response (≥30% reduction of proteinuria without renal progression) were recently proposed. We validated these criteria in a cohort of 125 patients with renal AL amyloidosis, mostly treated with bortezomib or lenalidomide. We confirmed the prognostic value of the renal staging system but also identified the limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 27 publications
3
58
0
9
Order By: Relevance
“…Of importance, 4/5 patients without a renal response had no hematological response and the fifth had only a partial hematological response. Three of these five patients had AL or AL/AH amyloidosis, a nephropathy characterized by its inconstant renal response to therapy . Our findings confirm that a complete hematological response is the main predictor for a prolonged renal response, but also that an early response is desirable.…”
Section: Discussionsupporting
confidence: 76%
“…Of importance, 4/5 patients without a renal response had no hematological response and the fifth had only a partial hematological response. Three of these five patients had AL or AL/AH amyloidosis, a nephropathy characterized by its inconstant renal response to therapy . Our findings confirm that a complete hematological response is the main predictor for a prolonged renal response, but also that an early response is desirable.…”
Section: Discussionsupporting
confidence: 76%
“…The Mayo Clinic group incorporated the dFLC level (with a cutoff value of 180 mg/L) in their revised staging system ( Figure 6B) 77,78 . A renal staging system predicting the progression to dialysis has also been proposed and validated by European investigators ( Figure 6C) 60,79 Although the severity of renal involvement does not directly affect survival, it impacts kidney survival, QOL and might reduce access to effective therapy. Other biomarkers have been shown to predict outcomes in systemic AL amyloidosis, but have not been integrated in staging systems so far.…”
Section: [H2] Patient Risk Stratificationmentioning
confidence: 99%
“…(Kumar et al , ; Dittrich et al , ; Milani et al , ; Sidana et al , ) In another series of 77 systemic AL amyloid patients with renal involvement, Wong et al () observed median dFLC levels 127 mg/l, with 60% of patients in this series having co‐existing cardiac involvement. Similarly, Kastritis et al () described a series of 125 patients with renal involvement, of whom 42% had co‐existing cardiac involvement. Median involved FLC levels were: 166 mg/l.…”
Section: Discussionmentioning
confidence: 93%